The mTOR cell signaling pathway is crucial to the long-term protective effects of ischemic postconditioning against stroke. (29th May 2018) - Wang, Peng; Xie, Rong; Cheng, Michelle; Sapolsky, Robert; Ji, Xunming; Zhao, Heng
Highlights: mTOR inhibition abolishes the long-term protection of postconditioning on injury size. mTOR inhibition inhibited protein expressions linked with axon growth and synaptic plasticity. mTOR promotion by S6K enhances protein expression linked with axon growth and synaptic plasticity. Abstract: Ischemic postconditioning (IPostC) protects against stroke, but few have studied the pathophysiological mechanisms of its long-term protective effects. Here, we investigated whether the mTOR pathway is involved in the long-term protective effects of IPostC. Stroke was induced in rats by distal middle cerebral artery occlusion (dMCAo) combined with 30 min of bilateral common carotid artery (CCA) occlusion, and IPostC was induced after the CCA release. Injury size and behavioral tests were measured up to 3 weeks post stroke. We used rapamycin and mTOR shRNA lentiviral vectors to inhibit mTOR activities, while S6K1 viral vectors, a main downstream mTOR gene, were used to promote mTOR activities. We found that rapamycin administration abolished the long-term protective effects of IPostC. In addition, IPostC promoted the presynaptic growth associated protein 43 (GAP-43) and the postsynaptic protein 95 (PSD-95) levels at 1 week post-stroke, which were reduced by rapamycin. Furthermore, rapamycin reduced phosphorylated mTOR (p-mTOR) protein levels measured at 3 weeks after stroke. These results were confirmed by mTOR shRNA transfection. Moreover, we found that injection of S6K1 viral vectors promoted GAP-43 and PSD-95 protein levels. We conclude that mTOR may play a crucial, protective role in brain damage after stroke and contribute to the protective effects of IPostC.